Blockchain-Enabled Wireless Sensor Networks for IoT Data Security and Integrity (Karapan Network Journal : Journal Computer Technology and Mobile Ad Hoc Network, 2025)
Wireless Sensor Networks (WSN) are an important component of the Internet of Things (IoT) that play a role in distributed environmental data collection. However, resource limitations and a generally centralized architecture make WSNs vulnerable to security attacks, particularly data manipulation and falsification, making it difficult to guarantee the integrity of IoT data. This study aims to design and evaluate the integration of blockchain technology in WSN to improve IoT data security and integrity without significantly compromising network efficiency. This research uses a quantitative experimental study approach by designing a Blockchain-Enabled Wireless Sensor Networks architecture consisting of sensor nodes, gateway nodes, and a blockchain network. The evaluation was conducted through simulations of various scenarios, including data manipulation, latency testing, energy consumption, communication overhead, throughput, and system scalability. The test results show that the blockchain-based WSN system is capable of detecting all simulated data manipulation scenarios through an immutable data hash recording mechanism. Blockchain integration increases latency and communication overhead compared to conventional WSNs, but sensor node energy consumption remains efficient because the blockchain process is run on gateway nodes. System throughput is relatively stable at medium network scales. This study shows that blockchain integration in WSN effectively improves the security and integrity of IoT data with an acceptable performance trade-off. The results obtained are in line with the research objectives, although scalability challenges still need to be optimized. Further research is recommended to explore lighter consensus mechanisms and the use of edge computing to support implementation in large-scale IoT networks.
Keywords: Keywords: Wireless Sensor Networks, Blockchain, Internet of Things, Data Security, Data Integrity